2018
DOI: 10.12659/msm.909640
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Inhibits Human Cervical Cancer Cells by Suppressing Protein Kinase C/Signal Transducer and Activator of Transcription (PKC/STAT3) Signaling Pathway

Abstract: BackgroundLike other human cancers, the malignancy of cervical cancer is also characterized by abilities of proliferation, migration, and invasion. Protein kinase C-zeta (PKCζ) has been highly correlated with several human cancers. Baicalin was proven to regulate PKC. This study aimed to investigate the anti-cancer effect and involved molecular mechanisms of baicalin on human cervical cancer.Material/MethodsBaicalin at various concentrations was used to treat 2 human cervical cancer cell lines HeLa and SiHa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The antiinflammatory activity of baicalin was also found in other cell cultures i.e. human arterial endothelial cells (HAECs) exposed to ischemia reperfusion injury [63], human chondrocyte cell line CHON-001 treated with IL-1β [64], human hepatocyte cell lβe [66], human cervical cancer cell lines HeLa and SiHa [67].…”
Section: Anti-inflammatory Activitymentioning
confidence: 68%
See 1 more Smart Citation
“…The antiinflammatory activity of baicalin was also found in other cell cultures i.e. human arterial endothelial cells (HAECs) exposed to ischemia reperfusion injury [63], human chondrocyte cell line CHON-001 treated with IL-1β [64], human hepatocyte cell lβe [66], human cervical cancer cell lines HeLa and SiHa [67].…”
Section: Anti-inflammatory Activitymentioning
confidence: 68%
“…So far, only one study on the effect of baicalin in preeclampsia (PE) has been carried out. Wang et al [67] pointed to the protective role of baicalin during injury of liver and kidney caused by PE in rat model. Baicalin were treated pregnant rats with PE in tree following doses: 50, 100, and 150 mg/kg/day, which were given by the intraperitoneal injection for 20 days.…”
Section: Influence In Pregnancymentioning
confidence: 99%
“…Therefore, reducing the expression of MMP-2 and MMP-9 or its upstream regulatory signaling pathways is essential for the treatment of malignant tumors. Up-regulation of MMP-2 and MMP-9 expression was mediated through various signaling pathways [8,9]. Here, we studied the novel pathways involved in PM-mediated MMP-2 and MMP-9 expression in the SCC4 and SCC25 human oral squamous cell carcinoma cell lines.…”
Section: Ivyspringmentioning
confidence: 99%
“…21 Baicalin (BA), also known as 7-glucuronic acid-5,6-dihydroxy-flavone, is a flavonoid isolated from Scutellaria baicalensis Georgi (Lamiaceae) and is broadly used as a herbal treatment for various inflammatory diseases in traditional Chinese medicine. 22,23 Previous studies revealed that BA exhibits widely potent biological activities, including anti-inflammatory, 24 antiviral 25 and antitumor effects, 26 etc. BA has been reported to suppress inflammation by inhibiting NF-κB, 27,28 which plays an essential role in the differentiation and function of osteoclasts.…”
Section: Introductionmentioning
confidence: 99%